Screening for Emergent Threats to Maternal and Newborn Health: A Literature Review - Morse, Avery; Mutiara Dewi, Aulia Ulfah; Farinisa, Aliva Nabila; Winarni, Sri; Kartasurya, Martha Irene (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractIntroduction: Though global trends for maternal and newborn mortality have improved, the COVID-19 pandemic had a negative impact on maternal and newborn health (MNH), increasing risk of complicated births. Indonesia’s Ministry of Health (IMOH) has made significant progress in expanding MNH services; however, challenges remain in improving screening for emergent threats (ET) to MNH, which includes emerging infectious diseases. This review aimed to compare antenatal care (ANC) standards in Indonesia to WHO guidelines and to evaluate the role of laboratory services and ultrasound (USG) for ANC.Methods: A narrative literature review was conducted through PubMed and Google Scholar. Articles were also found from the IMOH and the World Health Organization (WHO). Search terms included antenatal care, laboratory, ultrasound, and doppler, yielding sixteen articles in total. Nine articles published between 2010 and 2023 were included for review.Results: Compared to WHO standards of 8 ANC visits and 1 USG, Indonesia has a lower number of required ANC visits (6), but a higher requirement for USG visits (2); though, conflicting evidence exists for USG recommendations during pregnancy. One article evaluated standard laboratory tests administered during the first ANC visit, finding no records of testing at the puskesmas (primary healthcare center) level, while another cited improved infectious disease (ID) detection using screening questionnaires.Conclusion: In comparison to global standards, Indonesia may benefit from an increased number of ANC visits, ID screening in non-endemic areas, and studies on adherence to national screening guidelines. Further research is needed to evaluate the optimal timing of USG during the prenatal period.